STUNTING ANAK USIA SEKOLAH DI INDONESIA MENURUT KARAKTERISTIK KELUARGA - Salimar, Salimar; Kartono, Djoko; Fuada, Noviati Fuada; Setyawati, Budi (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2015)
ABSTRACT Stunting in childhood is associated with cognitive development, low productivity and shorter stature in adulthood. This analysis aimed to describe factors associated with stunting of school age (6-12 years) in Indonesia. The data used for analysis is cross-sectional data of Baseline Health Research (Riskesdas) in 2010. Study samples were all children aged 6-12 years who have complete data. The data were processed and presented in the form of tabulations and bivariate analysis. Logistic regression method was used to look at the factors of family characteristics that associated with stunting. Overall prevalence ofstunting among school-age children in Indonesia was 35.4 percent, 41.6 percent in rural areas 29.8 percent in urban areas. The prevalence of stunting of children of school age boys was 35.8 percent and girls was 35.0 percent. Factors associated with stunting in children of school age were family size, occupation of head of family, maternal education, and education of head of family. Keywords: school-age children, stunting, prevalence, family ABSTRAK Stunting pada masa anak-anak berhubungan dengan perkembangan kognitif, produktivitas yang rendah dan berperawakan pendek pada masa dewasa. Analisis data ini bertujuan mengetahui faktor-faktor yang berkorelasi dengan status gizi pendek (stunting) pada anak usia sekolah (6-12 tahun) di Indonesia. Penelitian ini merupakan analisis lanjut dari data Riset Kesehatan Dasar (Riskesdas) 2010, dengan disain potong_lintang, terhadap sampel semua anak berumur 6-12 tahun yang mempunyai data lengkap. Data diolah dan disajikan dalam bentuk tabulasi dan analisis bivariat. Untuk melihat faktor-faktor yang berhubungan dengan status gizi stunting pada anak usia sekolah, data dianalisis dengan regresi logistik. Total prevalensi stunting anak usia sekolah 35,4 persen (41,6 persen di perdesaan dan 29,8 persen di perkotaan). Prevalensi stunting anak laki-laki sebesar 35,8 persen dan anak perempuan sebesar 35,0 persen. Faktor-faktor yang berhubungan dengan status gizi (stunting) pada anak usia sekolah adalah besar keluarga, pekerjaan KK, pendidikan ibu, dan pendidikan KK). [Penel Gizi Makan 2013, 36(2):121-126] Kata kunci: anak usia sekolah, stunting, prevalensi, keluarga